2009
DOI: 10.2511/rpsd.34.3-4.102
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Emergent Literacy Skills Using Cultural Contextual Story-Based Lessons

Abstract: Recent statistics suggest that the number of Englishlanguage learners has been growing at a rapid rate in the United States. The growth of this population will inevitably lead to a larger number of culturally and linguistically diverse students with significant cognitive disabilities. Currently, there is little research on effective literacy practices, specifically for English-language learners with a moderate or severe intellectual disability. The participants in this study were one Latina paraprofessional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…If school systems still struggle in determining how to serve CLD students with high incidence disabilities then the question must be asked: How do we best serve CLD students with low incidence disabilities (i.e., moderate or severe ID)? CLD students with moderate or severe ID have faced many of the same issues as their nondisabled CLD peers (e.g., academic difficulties, postsecondary transition opportunities, language barriers); however, due to the nature of their disability, access to the general curriculum, appropriate services (e.g., translators), appropriate materials, and meaningful collaboration between families and educators may be more problematic (Kim & Morningstar, 2005;Mueller, Milian, & Lopez, 2009;Mueller, Singer, & Carranza, 2006;Spooner, Rivera, Browder, Baker, & Salas, 2009). What is equally worrisome is the lack of proper training faced by educators of CLD students with moderate or severe ID.…”
Section: Cld Students With Moderate or Severe Intellectual Disabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…If school systems still struggle in determining how to serve CLD students with high incidence disabilities then the question must be asked: How do we best serve CLD students with low incidence disabilities (i.e., moderate or severe ID)? CLD students with moderate or severe ID have faced many of the same issues as their nondisabled CLD peers (e.g., academic difficulties, postsecondary transition opportunities, language barriers); however, due to the nature of their disability, access to the general curriculum, appropriate services (e.g., translators), appropriate materials, and meaningful collaboration between families and educators may be more problematic (Kim & Morningstar, 2005;Mueller, Milian, & Lopez, 2009;Mueller, Singer, & Carranza, 2006;Spooner, Rivera, Browder, Baker, & Salas, 2009). What is equally worrisome is the lack of proper training faced by educators of CLD students with moderate or severe ID.…”
Section: Cld Students With Moderate or Severe Intellectual Disabilitymentioning
confidence: 99%
“…The consistency of these instructional trials may be implemented by various individuals and should include operationalized procedures (e.g., specific prompts, schedule for fading prompts, feedback for correct and incorrect responses). Similarly, systematic and explicit instruction is also critical for CLD students with moderate or severe ID (Spooner et al, 2009). Although we should not limit ourselves to behavioral forms of instruction (Banks, Sapp, & Obiakor, 2013), considering the diversity among students, research has demonstrated the benefits of systematic and explicit instruction for a wide range of students (e.g., Haager & Klingner, 2005;Klingner & Vaughn, 2000).…”
Section: Universal Design For Learning (Udl)mentioning
confidence: 99%
See 3 more Smart Citations